PENGARUH LIKUIDITAS, LEVERAGE DAN INTENSITAS ASET TERHADAP AGRESIVITAS PAJAK - Diah Amalia (KRISNA: Kumpulan Riset Akuntansi, 2021)
One of the sources of State revenue is from the tax sector, the state income plays an important role in national development. Optimization in tax revenue has many obstacles, one of which is a form of non-compliance in paying taxes, researchers take the factor of liquidity, leverage, intensity of fixed assets and inventory intensity to determine the effect on tax aggressiveness. This study aims to examine the effect of liquidity, leverage, and intensity of fixed assets on tax aggressiveness in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2013-2017. Through a purposive sampling method, researchers obtained 60 sample companies. The data analysis technique used is multiple linear analysis. The research results obtained are leverage factors that influence the level of corporate taxpayer aggressiveness while the liquidity factor, the intensity of fixed assets does not affect the level of tax aggressiveness